GENDER DIFFERENCES IN BORDERLINE PERSONALITY DISORDER FEATURES IN AN EPIDEMIOLOGICAL SAMPLE OF ADULTS AGE 55–64: SELF VERSUS INFORMANT REPORT - Busch, Alexander J. (J Pers Disord, 2015)
The literature on the prevalence of borderline personality disorder (BPD) across gender reveals multiple trends. A number of studies indicate that women have a higher prevalence. Others indicate no difference, and a few even reveal that men have a higher prevalence. Yet existing studies are plagued by sampling biases, use mainly self-reported information, and tend to report general prevalence of BPD categorically defined. The current investigation attempted to shed new light on this literature by analyzing BPD features dimensionally in a representative epidemiological sample of adults ages 55–64, using both self- and informant-reported perspectives. Data from the St. Louis Personality and Aging Network study revealed a significant interaction across gender and perspective, F(1, 1360) = 23.46, p < .01. Gender differences were found for self-report only, such that men reported greater BPD severity. Meanwhile, informant report indicated no gender difference. Trends underscore the importance of epidemiological sampling and multiple assessment perspectives when analyzing BPD.